Analyzing the Impact of Geopolitical Risk, and Renewable Energy Towards Sustainable Development in China - Farooq, Fatima; Tanveer, Arsalan; Faheem, Muhammad (iRASD Journal of Economics, 2023)
Geopolitical relationship among the economies plays a crucial role in the environmental sustainability. In lieu our research reveals that whether geopolitical risk asymmetrically affects the reduction of carbon emission? To investigate this issue, we scrutinize the impact of geopolitical risk using annual data spanning 1990-2018 for China. Furthermore, our study employs nonlinear and liner autoregressive distributed lag simulations at the same time to argue the impact of geopolitical risk on environmental sustainability. Our empirical outcomes evidenced the asymmetric effect of geopolitical risk on the environment by indicating a positive association among geopolitical risk and environmental sustainability. Moreover, increasing foreign direct investment upsurges CO2 emanation which proves the pollution haven proposition. The results expressed a significant positive link of energy ingesting and GDP influence on CO2 emanation while renewable energy consumption reduces CO2 emission. Therefore, utmost attention must be taken to balance the environment and geopolitical risk. It is necessary to take initiatives to reforms policies that protect the environment without affecting geopolitical risk. Additionally, government officials and policymakers should articulate strategies to encourage renewable energy consumption as the energy combination outpouring to enrich the excellence of the environment. The findings also advocate that policymakers to welcome the environment-friendly foreign direct investment as it is the perpetrator to upsurge environmental degradation in China.